GENDER AND GRAMMATICAL ERRORS IN ENGLISH ACADEMIC PAPERS: A STUDY AT ENGLISH GRADUATE DEPARTMENT OF MATARAM UNIVERSITY - Al Idrus, Sy. Fatimatuzzahra (Widya Balina, 2023)
The study aimed at identifying and analyzing students stylistic errors in the form of grammatical errors made by male and female students of English Graduate Department of Mataram University. This research is focused on finding the significant differences between male and female students in terms of the percentages of grammatical errors in their academic papers and factors contributing the errors. The sample of this research was 20 papers of 10 male and 10 female students of English Graduate Department of Mataram University. The data were interpreted and analyzed by quantitative descriptive analysis using Pearson chi-square to investigate if there were any significant differences among the percentage of grammatical errors in each category and then the types of grammatical errors in the two groups of male and female students were compared by use of descriptive analysis and statistical analysis. The research findings show: The result of Pearson Chi-square test of students grammatical-related stylistic error subcategory, χ2count= 5.43 and χ2table= 11.07.It means that the χ2 Count < χ2 table and the null hypothesis H0 was failed to be rejected. It means there was no difference between male and female students in terms of percentage of grammatical-related stylistic errors sub-category in their academic papers at the level of significance a = 5%. (2) Based on the data analysis, retrospective interview, both cognitive and social factors are affected the students’ ability in writing an academic paper. The cognitive factor was the lack knowledge of male and female students about academic writing style and register. This is caused by the lack information they got in their previous study. Therefore, the male and female students still have weaknesses for writing in academic context.